(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
“The police officer is an instrument for the prevention and detection of crime’’1Police play a key role in fighting crime, preserving peace, maintaining public order. They basically play a dual role while maintaining the law and order of any state. The head of the provincial police department is the Director-General of the police and in all provinces take the Legislature-The Police Officer.